Single-center pharmacokinetic study and simulation of a low meropenem concentration in brain-dead organ donors - Lee, Jae Myeong; Lee, Joo Won; Jeong, Tae Seok; Bang, Eun Sook; Kim, So Hee (Antimicrobial Agents and Chemotherapy, 2018)
Meropenem is an ultrabroad-spectrum antibiotic of the carbapenem family. In brain-dead organ donors, administration of standard meropenem dosages does not reach therapeutic levels. Our objectives were to determine the plasma concentration of meropenem after the administration of standard meropenem dose and to estimate an improved dosage regimen for these patients. One gram of meropenem was administered as a 1-h infusion every 8 h for 1 to 3 days, and blood samples were collected. The plasma concentration of meropenem was measured and subjected to pharmacokinetic analysis. Simcyp simulation was performed to predict the optimum plasma levels and dosage based on the patients' individual pharmacokinetic parameters. The maximum plasma concentration of meropenem was 3.29 μg/ml, which was lower than four times the MIC of 8 μg/ml. Although the mean creatinine clearance of patients was moderately low (67.5 ml/min), the apparent volume of distribution at steady state (Vss) and time-averaged total body clearance (CL) of meropenem were markedly elevated (4.97 liters/kg and 2.06 liters/h/kg, respectively), owing to massive fluid loading to decrease the high sodium levels and to treat shock or dehydration. The simulation revealed that dose and infusion time of meropenem should be increased based on patients' Vss and CL, and a loading dose is recommended to reach rapidly the target concentration. In conclusion, a standard meropenem regimen is insufficient to achieve optimal drug levels in brain-dead patients, and an increase in dose and extended or continuous infusion with intravenous bolus administration of a loading dose are recommended for these patients.
Keywords: Adult; Aged; Anti-Bacterial Agents; Brain Death; Female; Humans; Male; Meropenem; Microbial Sensitivity Tests; Middle Aged; Monte Carlo Method; Tissue Donors; Brain-dead organ donors; Meropenem; Optimal therapeutic level; Pharmacokinetics; Simcyp simulation